For the Sake of the Child: Quality of Spousal Relationship Impact on the Early Education of Their Child - Mathwasa Joyce (Randwick International of Social Science Journal, 2020)
The moral fibre of the nation depends on the quality of parenting which entails emotional development, personality and behavioural moulding that fosters well-adjusted individuals. This study set out to assess how the quality of spousal relationship impacts on the early education of children. The study espoused the interpretive paradigm within the qualitative approach to consult participants in their natural environment. The emotional security hypothesis theory was adopted to understand the impact marital conflict to child learning. Purposively selected were two couples, two single males, two single female parents and two educators who responded to semi-structured interviews. Adherence to ethical issues was confirmed by signing of the consent forms. Data was recorded per emerging themes. The findings exposed the diminishing returns on school achievement, exhibition of delinquent behaviour and maladjusted adolescents due to lack of stability in the early education of children. The findings also revealed that some spouses and partners begrudgingly disconnect themselves from the children for the sake of peace. The study recommends conflict resolution strategies that encourage amicable co-parenting for unmarried partners for the sake of the child.